Diagnostic Accuracy Of Sputum Microscopy Versus Gene-Xpert In Diagnosis Of Pulmonary Tuberculosis (Journal of Pharmaceutical Negative Results, 2022)
Background: Tuberculosis also known as TB is a severe contagious disease that is caused by Mycobacterium species that mainly targets the respiratory organs particularly the lungs. Quick and appropriate diagnosis is critical in the management and prevention of the diseases. This work aims at establishing which diagnostic method is efficient in diagnosing pulmonary TB at secondary health care facilities in KWGH; sputum microscopy against GeneXpert.Objective: To determine the diagnostic performance of sputum microscopy compared to GeneXpert in estimating the TB burdenamong clinically suspected PL TB patients to determine the capability of microscopy to continue as the first-line test.Study Design: A cross sectional study.Place and Duration of study: Department of Pulmonology, Lady Reading Hospital, Peshawar. 6 months from 31/8/2020 to 29/2/2021Methods: Bronchial wash samples and sputum was taken from the patients. Of the samples, three samples were analyzed through microscopy while the other through GeneXpert. Patients’ liver and renal profiles and color vision acuity and serum uric acid level were also checked before commencing the treatment.Results: In overall 209 patients included in the study, the patients’ mean age was 41 years (+/- 10. 91). A previous study by this author was also conducted on a sample of 200 respondents of which 64% were male and 36% female. In the distribution of age and gender the p-value was greater than 0. 05 thus depicting that it’s statistically insignificant. The sensitivity of sputum microscopy was found to be 76. 88 % while specificity was 80. 00%; the positive predictive value was 98. 70 % and negative predictive value was 14. 81% with overall diagnostic accuracy of 77. 03% was also found in this study.Conclusion: Sputum microscopy has moderate sensitivity and high specificity but a comparatively low NPV for confirming exclusion of PTB. Based on these observations, GeneXpter should be incorporated into the second-tier health facilities to enhance the efficiency of TB diagnosis and consequently patients’ improvement.